A Case Study: Lessons from the Hong Kong Independent Commission Against Corruption - Hsieh, Ming Li (International Journal of Criminology and Sociology, 2016)
This article is a case study that examines the three-pronged approach (TPA) of the Independent Commission against Corruption (ICAC) in Hong Kong. Its functions and operations on anti-corruption matters will be assessed from an institution-oriented perspective. It is suggested that for decades, the TPA had been misunderstood in its role as a conventional investigation, prevention and education tool and that such misconceptions may lead to a failure in anti-corruption institutional reform. By better understanding the TPA and its simplistic traits of deterrence and trust then we may be able to remedy the misconceptions the public has about ICAC’s strategies. Policy implications involve further improvements in anti-corruption agencies that will enhance their role in maintaining an environment free of corruption.